URGENSI LARANGAN PERKAWINAN SATU MARGA PADA MASYARAKAT DESA SIGAMA UJUNG GADING KECAMATAN PADANG BOLAK KABUPATEN PADANG LAWAS UTARA - Darwis Harahap; Maria Kaban; Rosnidar Sembiring (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Sigama Village, Ujung Gading, still applies severe customary sanctions to those who practice same-marriage marriages, even though the marriage is legally valid and not prohibited. Sanctions such as large fines, social exclusion, revocation of inheritance rights, and prohibitions on participating in customary activities are still enforced because the community believes that same-marriage marriages bring shame, disaster, and disrupt kinship order. This situation creates tension between custom and positive law, while also showing the difference between general Batak customary rules and specific customary practices in the village. Therefore, this issue is important to study to see the extent to which these customary prohibitions and sanctions are still relevant in today's community life. Using a normative juridical method that examines documents related to the research problem. The results of the study show that the Batak Angkola customary marriage in Paluta still prohibits same-marriage marriages because they are considered to violate customary order, even though state law does not prohibit it. As a result, tension arises between custom and positive law, especially regarding social status and inheritance rights. Perpetrators of same-marriage marriages often receive customary sanctions such as fines and ostracism. This situation demonstrates that society is still striving to maintain traditions amidst modern social change.   Keywords: Marriage, Customary Law, Legal Consequences   Abstrak: Desa Sigama Ujung Gading masih menerapkan sanksi adat yang berat terhadap pelaku perkawinan semarga, meskipun secara hukum negara perkawinan tersebut sah dan tidak dilarang. Sanksi seperti denda besar, pengucilan sosial, pencabutan hak waris, hingga larangan mengikuti kegiatan adat tetap diberlakukan karena masyarakat meyakini bahwa perkawinan semarga membawa aib, musibah, dan mengganggu tatanan kekerabatan. Situasi ini menimbulkan ketegangan antara adat dan hukum positif, sekaligus menunjukkan adanya perbedaan antara aturan adat Batak secara umum dengan praktik adat khusus di desa tersebut. Oleh karena itu, persoalan ini penting dikaji untuk melihat sejauh mana larangan dan sanksi adat tersebut masih relevan dalam kehidupan masyarakat saat ini. Dengan metode yuridis normatif yang mana meneaalha dokumen-dokuman yang berkaitan dengan masalah penelitian. Hasil penelitian  menunjukkan bahwa Perkawinan adat Batak Angkola di Paluta tetap melarang perkawinan semarga karena dianggap melanggar tatanan adat, meskipun hukum negara tidak melarangnya. Akibatnya muncul ketegangan antara adat dan hukum positif, terutama terkait status sosial dan hak waris. Pelaku perkawinan semarga sering menerima sanksi adat seperti denda dan pengucilan. Situasi ini menunjukkan bahwa masyarakat masih berusaha mempertahankan tradisi di tengah perubahan sosial modern.   Kata Kunci: Perkawinan, Hukum Adat, Akibat Hukum